Trade relation between France and the Czech Republic - Drápal, Filip; Štěrbová, Ludmila, 1957-; Müller, David, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This bachelor thesis focuses on the trade relations between France and the Czech Republic. The main objective is to understand the structure of these two economic environments, the reasons behind French trade deficit with the Czech Republic and outline further development. The first part concentrates on macroeconomic environment of both countries. In the second section, an analysis of trade and investment flows from the perspective of their development since 1989 can be found. In the third and the last part, the bachelor thesis concentrates on selected branches in perspective fields with concrete examples where mutual cooperation already exists and can be further developed in the upcoming years.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses